Correcting the Incorrect: an Exploratory Study into the Role of the Controller in Counteracting Financial Fake News - Veldman, W.; Swagerman, D. M. (Archives of Business Research, 2018)
This study aims to provide a foundation for an initial exploratory theory about the role of the controller in counteracting financial fake news. To accomplish this, the efforts against the dissemination of financial fake news were explored at the overall, societal, segmental, firm and function level. The Constructivist Grounded Theory Method is used to generate a conceptual model out of those five levels of analysis. As part of this approach, data from open interviews with ten respondents and key informants are used to gain insights into the efforts against the phenomenon of financial fake news. Thereafter, the results were analysed in a phenomenological oriented way to draw conclusions from it. This study concludes that the rational considerations one makes to discover to truth are embedded in the role of the controller as ‘being the conscience of the firm’. Nevertheless, financial fake news is a complex phenomenon that is rather an assessment or judgement than a measurable fact, whereby its complexity stems from the phenomenon’s multidimensional characteristics. Possible misconceptions regarding news can arise due to ignorance of reality. Therefore, intervention in the form of countermeasures is of importance from a social point of view. On the contrary, it can be questioned whether these interventions are necessary from an economic point of view, since general benefit of society at large is created when everyone is pursuing their own interests. The way in which financial fake news should be counteracted thus depends on the perspective in which the problem is approached.